Criptomonedas ¿paradigma moderno o discusión sin alcance práctivo? (2019)
In this review article the problem of virtual currencies is addressed, its juridification by some states and, particularly, the legal-fiscal position taken by the Colombian state. This is the basis to understand if it’s necessary or not to recognize the cryptocurrency issue as a modern paradigm that affects the public financial right, or just, is a mere theoretical discussion with no practical scope.